An evaluation of the impact of disciple-making on work ethic of Ghanaian Christians : a case study of the Church of Pentecost Ghana - Gakpetor, Sam (Stellenbosch : Stellenbosch University, 2023)
Thesis (PhD)--Stellenbosch University, 2023.